Risk Assessment in Pregnant Women with Congenital Heart Disease: A Meta-Analysis Study - Alanazi, Noof Falah; AlSaedi, Amal Salman N; Alshammari, HANA fazi; Faden, Lujain Mamoon; Khan, Reem Mahmoud (Journal of Posthumanism, 2025)
Pregnant women with congenital heart disease (CHD) have a significantly increased risk of cardiovascular complications. Prediction of patients at the highest risk of life-threatening complications remains a major challenge (Chu et al., 2020). A meta-analysis has been conducted to examine the risk assessment of pregnant women with CHD to provide useful information and treatment guidelines concerning the associated risk.The search protocol involved literature published on established databases before September 2023. The combined risk and 95% confidence intervals (CIs) of pregnant women with CHD suffering from cardiovascular complications were analysed; the risk of preterm labor and small for gestational age (SGA) in women with CHD was also assessed. The analysis included 29 studies of 19,647 pregnant women with CHD. The risk of pregnant women with CHD suffering from cardiovascular complications was 3.90 (95% CI, 2.90–5.24). The risk of preterm labour in pregnant women with CHD was 1.82 (95% CI, 1.39–2.38), and the risk of SGA was 1.50 (95% CI, 1.13–1.99) (Dhiman et al., 2024). Owing to the high incidence of adverse events, pregnant women with CHD require more frequent prenatal examinations, and healthcare professionals should provide timely interventions to effectively ensure maternal and fetal safety (Regitz-Zagrosek et al., 2018; Siu & Colman, 2019).